Florida Solid and Hazardous Waste Regulation Handbook: Overview - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
Federal law regulating the management of solid and hazardous wastes can be found in many different acts of Congress. The Resource Conservation and Recovery Act (RCRA) affects waste management, as does the Comprehensive Environmental Response, Compensation, and Liability Act (CERCLA) and the Federal Insecticide, Fungicide and Rodenticide Act (FIFRA). No single comprehensive federal law for solid and hazardous waste management exists, although RCRA touches on most of the major issues. This is EDIS document FE442, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.